Kingella infections in children – a child with small ventricular septal defect and endocarditis. (4th April 2011) - Abraham, D; Garbe, F; Dotse, S; Venugopalan, P
Abstract : Aim: To study the prevalence of Kingella infections in children under 18 years in a District General Hospital in the UK. Methods: The records of the microbiology laboratory over a 10-year period (2001–2010) were reviewed to identify cases under 18 years of age with a positive blood or synovial fluid culture for Kingella Kingae. The case notes of children with positive culture were analysed to obtain data regarding diagnosis, mode of presentation, clinical features, results of other investigations and final outcome. Results: Only one child with Kingella Kingae positive blood culture was identified. This 3-year old child had a small perimembranous ventricular septal defect (VSD), and presented with a short febrile illness and oral blisters. In view of her VSD, she was worked up for infective endocarditis, however blood cultures did not yield any growth in the first 72 h and she responded rapidly to antibiotic therapy. She was therefore discharged home on oral antibiotics. On day 4, her blood cultures isolated a significant growth of Kingella Kingae and the child was re-admitted. An echocardiogram performed demonstrated a 3.3 mm × 2.7 mm vegetation attached to the septal leaflet of the tricuspid valve. The child made good recovery with intravenous antibiotic therapy. Conclusion: Kingella infections are rare in children. In our study, only one child had a documented infection with the microbe during the10-year study period; however this child suffered from endocarditis, a potentially life-threatening infection complicating a pre-existing small VSD. Our case highlights the need to maintain a high index of suspicion for infective endocarditis with organisms of low virulence in febrile children with VSD, even when they appear well otherwise. We would also like to emphasise that even small VSDs are prone to bacterial endocarditis, to a similar degree as large VSDs. This information is interesting in the context of recently published guidelines on endocarditis prophylaxis.